FEAR-RELATED PROBLEMS IN MILITARY PERSONNEL - Safarov Hamza Jo‘raevich (American Journals, 2022)
In this article, the problems and stress caused by the feeling of fear in military personnel, and opinions on how to overcome it were expressed.
Keywords: Fear, mental state, stress, military, psychological method, psychological effect.